2004
DOI: 10.1039/b303986m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on uptake and photodynamic action of chlorin p6 on human colon and breast adenocarcinoma cell lines

Abstract: The effect of reducing the extracellular pH from 7.4 to 6.0 on the uptake and photosensitivity of chlorin p6, a potential photosensitising drug, has been investigated using two mammalian cell lines, human colon (Colo-205) and breast (MCF-7) adenocarcinoma cells. In Colo-205 cells, the uptake and phototoxicity of chlorin p6 was observed to increase as the pH of the incubation medium decreased. For light doses of up to [similar]6 kJ m(-2), although there was no evidence of mitochondrial damage, a significant red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…Böhmer and Morstyn (1985) showed that the uptake of hematoporphyrin derivative from normal and malignant cells increased when the medium pH was decreased from 7.4 to 6.0. This effect was also described by Sharma et al (2004), who demonstrated that both the uptake and phototoxicity of chlorin p6 were increased as the pH of the incubation medium decreased, in human colon adenocarcinoma cells. Uzdensky et al (2007) recently studied the involvement of Ca 2+ -mediated signaling pathways in photooxidative injury of neurons and glia.…”
supporting
confidence: 55%
“…Böhmer and Morstyn (1985) showed that the uptake of hematoporphyrin derivative from normal and malignant cells increased when the medium pH was decreased from 7.4 to 6.0. This effect was also described by Sharma et al (2004), who demonstrated that both the uptake and phototoxicity of chlorin p6 were increased as the pH of the incubation medium decreased, in human colon adenocarcinoma cells. Uzdensky et al (2007) recently studied the involvement of Ca 2+ -mediated signaling pathways in photooxidative injury of neurons and glia.…”
supporting
confidence: 55%
“…The accumulation of chlorin e6 in A549 and A549/CDDP cell lines at 4°C was significantly lower than that at 37°C, indicating the temperature dependence of the uptake of chlorin e6 in these cell lines. Involvement of passive diffusion and/or the endocytic pathway in chlorin e6 uptake has been indicated,29–31 but the molecular mechanisms underlying the cellular uptake remain to be fully elucidated. Recently, chlorin e6 and hematoporphyrin were reported to competitively inhibit the organic anion transporting polypeptide 1B1 (OATP1B1)‐mediated uptake,32 although the paper did not show whether the photosensitizers are transported by OATP1B1.…”
Section: Discussionmentioning
confidence: 99%
“…This enabl Cp 6 has three ionizable carboxylic a protonation-deprotonation of the three Figure 5. r as it has a strong absorption band at ~660 nm which ood triplet yield and good tumor selectivity [16][17][18][19]. Our p eritoneally administered free Cp 6 can cause complete nec e <100 mm 3 in hamster cheek pouch animal model [20] ug, only superficial necrosis and size reduction was observ used to achieve higher drug delivery in tumor because o led complete regression of bigger tumors ( 1000 mm 3 ).…”
Section: Interaction With Chlorin-p6(cp 6 )mentioning
confidence: 91%
“…In aqueous medium at physiological pH the drug exists predominantly as negatively charged (i.e. closer to structure D in Figure 5) and as the pH is progressively lowered, successive protonation of the carboxyl groups (forming structures C to A in Scheme 1) makes it hydrophobic leading to aggregation of the drug which has been shown to enhance its uptake in human colon adenocarcinoma (Colo-205) cells [19]. The change in acid/base ionization equilibrium of the PS also leads to significant changes in its absorption and fluorescence characteristics.…”
Section: Interaction With Chlorin-p6(cp 6 )mentioning
confidence: 98%